Development of Multiple Representation-Based E-Modules Utilizing Augmented Reality in the Material of Molecular Shapes and Inter-Molecular Interactions - Sherly Aulia; Lenny Anwar S; Roza Linda (AL-ISHLAH: Jurnal Pendidikan, 2023)
The goal of this research was to create an e-module based on multiple representations in the material of molecular shapes and interactions between molecules using augmented reality technology. The method used is the Research and Development (RD) method with the ADDIE model, which consists of 5 phases: the analysis phase, the design phase, the development phase, the implementation phase, and the evaluation phase. Data collection techniques include interviews, student questionnaires, validation sheets, and user response questionnaires. Two methods were used in small-scale trials: one-on-one testing and user response. The one-on-one test involves three students with high, medium, and low abilities. The data obtained from the interviews are in the form of supporting questions related to opinions on the use of teaching materials, followed by assessments of questionnaire sheets and validation sheets in the form of scales. The type of scale used is a Likert scale with a score of 1-4. User response assessment involved three teachers and 30 students. The results showed that the developed e-module obtained an average percentage of material experts (95.7%) and media experts (92.2%), with very valid criteria; a one-on-one test to get students' comments for e-module components that must be repaired; and user responses, (namely teachers and students), with percentages of 93.1% and 93.7%, with very good criteria.